2010
DOI: 10.1007/s00268-010-0748-1
|View full text |Cite
|
Sign up to set email alerts
|

Colorectal Cancer in Young Patients in Israel: A Distinct Clinicopathological Entity?

Abstract: Colorectal cancer in young patients was found to display a cluster of unique characteristics but fewer than previously reported and young age by itself was not found to impact patient outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 25 publications
1
7
0
Order By: Relevance
“…Second, as opposed to some large registry-based studies, which might lack important data, we extracted very detailed clinical data from the patients’ individual medical files. Third, in contrast to other studies evaluating elderly patients with CRC which included much lower age cut-off[ 9 , 10 , 12 , 13 , 19 , 27 , 34 , 38 ], this study’s cut-off probably might highlighted the differences between older and the younger population better.…”
Section: Discussionmentioning
confidence: 81%
“…Second, as opposed to some large registry-based studies, which might lack important data, we extracted very detailed clinical data from the patients’ individual medical files. Third, in contrast to other studies evaluating elderly patients with CRC which included much lower age cut-off[ 9 , 10 , 12 , 13 , 19 , 27 , 34 , 38 ], this study’s cut-off probably might highlighted the differences between older and the younger population better.…”
Section: Discussionmentioning
confidence: 81%
“…Of course some studies demonstrated that, in younger ages, the cancer is presented with different features (anatomical site, stage of tumor, etc. ), but young age by itself was not found to impact patient outcome [16, 18]. …”
Section: Discussionmentioning
confidence: 99%
“…Second, as opposed to some large registrybased studies, which might lack important data, we extracted very detailed clinical data from the patients' individual medical files. Third, in contrast to other studies evaluating elderly patients with CRC which included much lower age cutoff [9,10,12,13,19,27,34,38] , this study's cutoff probably might highlighted the differences between older and the younger population better.…”
Section: Discussionmentioning
confidence: 61%